Evaluation of ERINA Plus as a coat conditioner in canines - Srivastava; P.C. and Bhagwat; V.G. (Veterinary World, 2008)
Coat conditioning, deodorant and cleansing properties of ERINA Plus were evaluated in fifty-one dogs of different breeds. More than 80% of dogs showed good to excellent conditioning, deodorant and cleansing effects supported ERINA Plus as safe conditioner shampoo. [Vet. World 2008; 1(12.000): 361-362]